2021
DOI: 10.3390/jpm11010030
|View full text |Cite
|
Sign up to set email alerts
|

Digital Interventions for Psychological Comorbidities in Chronic Diseases—A Systematic Review

Abstract: Chronic diseases represent one of the main causes of death worldwide. The integration of digital solutions in clinical interventions is broadly diffused today; however, evidence on their efficacy in addressing psychological comorbidities of chronic diseases is sparse. This systematic review analyzes and synthesizes the evidence about the efficacy of digital interventions on psychological comorbidities outcomes of specific chronic diseases. According to the Preferred Reporting Items for Systematic Reviews and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 86 publications
0
19
0
1
Order By: Relevance
“…Although patients with diabetes can make use of several apps and at least some (web-based) diabetes education programs that help in disease management [ 30 , 31 ], only a few web-based e-mental health interventions exist. A recent systematic review from 2021 found 9 studies offering digital interventions for psychological comorbidities in patients with diabetes [ 32 ]. Two of these studies were conducted in Germany [ 33 , 34 ] and both offered the guided self-help web-based intervention GET.ON Mood Enhancer Diabetes for depression in people with diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Although patients with diabetes can make use of several apps and at least some (web-based) diabetes education programs that help in disease management [ 30 , 31 ], only a few web-based e-mental health interventions exist. A recent systematic review from 2021 found 9 studies offering digital interventions for psychological comorbidities in patients with diabetes [ 32 ]. Two of these studies were conducted in Germany [ 33 , 34 ] and both offered the guided self-help web-based intervention GET.ON Mood Enhancer Diabetes for depression in people with diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Scientific literature suggests that mHealth solutions, including mobile applications (apps), help manage a CD [ 13 , 14 ], including its possible comorbidity with other psychological problems [ 15 ]. In particular, the changes in CD patients’ lifestyle through the use of the mHealth apps are remarkable, mainly in adherence to regular exercise, healthy diet and body weight [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In response to this need, recent digital health models may constitute optimal solutions. Thanks to the adoption of mobile devices and healthcare platforms, the telerehabilitation (TR) approach allows care to overcome accessibility and cost barriers, potentially scaling up the service to a broader population [ 11 , 12 , 13 ]. A recent meta-analysis [ 14 ] on randomized and non-randomized trials supported the non-inferiority effect of TR compared to hospital-based interventions in the COPD population.…”
Section: Introductionmentioning
confidence: 99%